KLAUS SCHWAB’S “THE FOURTH INDUSTRIAL REVOLUTION” AND THE DISCUSSION OF ISSUES RELATED TO ARTIFICIAL INTELLIGENCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the issues related to artificial intelligence as discussed in Klaus Schwab’s book The Fourth Industrial Revolution.